A face like glass - Hardinge, Frances (Amulet Books, 2018)
The people in the underground city of Caverna live their lives with expressionless faces, and must be taught how to express emotions by Facesmiths, who charge a steep price for the ability. A young girl named Neverfell, who has no memory of her past, must wear a mask at all times because of her natural ability to express herself--an ability that makes her dangerous to the people of Caverna.